Extentions between admissible representations of isometry groups of regular trees - Demir, Selcuk (Springer, 2006)
This is the continuation of our previous work (Demir, Geom. Dedicata 105, 189-207, 2004). In this paper, we study extensions between admissible representations of the isometry groups of regular trees. We use the results of Demir, (Geom. Dedicata 105, 189-207, 2004) to show, following Schneider and Stuhler (J. Reine. Angew. Math. 436, 19-32, 1993) in the p-adic case, that extensions between admissible representations of G are finite-dimensional.
Keywords: Category Of Smooth Representations; İsometry Groups Of Regular Trees